A clinically novel AIP mutation in a patient with a very large, apparently sporadic somatotrope adenoma - Salvatori, Roberto (Bioscientifica Ltd, 2014)
Heterozygous germline inactivating mutations in the aryl hydrocarbon receptor-interacting protein (AIP) gene lead to pituitary adenomas that most frequently present in the setting of familial isolated pituitary adenoma syndrome, usually as somatotropinomas and prolactinomas. More recently, they have been found in a significant percentage of young patients presenting with pituitary macroadenoma without any apparent family history. We describe the case of a 19-year-old man who presented with a gigantic somatotropinoma. His family history was negative. His peripheral DNA showed a heterozygous AIP mutation (p.I13N), while tumor tissue only had the mutated allele, showing loss of heterozygosity (LOH) and suggesting that the mutation caused the disease. LEARNING POINTS: AIP mutations may be observed in sporadic somatotrope adenomas occurring in young patients. LOH is a strong indicator that an AIP variant is disease causing. Somatotrope adenomas in carriers of AIP mutations are generally larger and more difficult to cure.